2022
DOI: 10.3389/fendo.2022.915279
|View full text |Cite
|
Sign up to set email alerts
|

Semiquantitative assessment of 99mTc-MIBI uptake in parathyroids of secondary hyperparathyroidism patients with chronic renal failure

Abstract: ObjectiveTo explore the valuably influential factors and improve the diagnostic accuracy and efficiency of 99mTc-methoxyisobutylisonitrile (MIBI) uptake in parathyroids of secondary hyperparathyroidism (SHPT) patients with chronic renal failure (CRF).MethodsThe correlation analysis was performed between clinical indices related to CRF and 99mTc-MIBI uptake intensity TBR (the gray value mean ratio between the parathyroid target and the bilateral neck background, semiquantitatively calculated with ImageJ softwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The imaging principle is based on the abundance of mitochondria in hyperfunctioning parathyroid tissue, where MIBI can accumulate 7 . MIBI uptake was significantly positively correlated with patient age, duration of chronic renal failure, years on hemodialysis, serum parathyroid hormone, and alkaline phosphatase, but negatively correlated with serum uric acid 8 …”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The imaging principle is based on the abundance of mitochondria in hyperfunctioning parathyroid tissue, where MIBI can accumulate 7 . MIBI uptake was significantly positively correlated with patient age, duration of chronic renal failure, years on hemodialysis, serum parathyroid hormone, and alkaline phosphatase, but negatively correlated with serum uric acid 8 …”
Section: Discussionmentioning
confidence: 93%
“…7 MIBI uptake was significantly positively correlated with patient age, duration of chronic renal failure, years on hemodialysis, serum parathyroid hormone, and alkaline phosphatase, but negatively correlated with serum uric acid. 8 Tc-99m-MIBI duplex imaging is a more commonly used functional imaging diagnostic method for parathyroid disease today, and has unique value compared to other imaging examinations in helping to localize one or more parathyroid lesions, especially for ectopic glands that cannot be identified by ultrasound, with a higher detection rate than ultrasound. A comparative study involving 60 patients demonstrated that early Tc-99m-MIBI SPECT/CT has superior ability to detect parathyroid lesions in Secondary hyperparathyroidism patients compared to ultrasound, dual-phase Tc-99m-MIBI scintigraphy, and delayed Tc-99m-MIBI SPECT/CT.…”
Section: Discussionmentioning
confidence: 99%
“…The higher RI may be explained by the lower expression of the P-glycoprotein and multidrug resistance-associated protein 1 (MRP1), which transport drugs and their metabolites across the cell membrane [ 19 , 68 ]. Whether this may apply to PC in SHPT remains unclear, especially as parathyroid MIBI uptake in SHPT is reduced by the administration of calcitriol and calcium, and MIBI uptake and washout correlate with parameters related to CKD (higher uptake and lower washout with longer dialysis vintage and higher PTH and Ca x P product) [ 69 ].…”
Section: Discussionmentioning
confidence: 99%